ANALISIS KEBUTUHAN SISWA DALAM PENYUSUNAN PROGRAM LAYANAN BIMBINGAN DAN KONSELING - Muhammad Rahmad; M. Husen; Fajriani Fajriani (Program Studi Bimbingan dan Konseling, FKIP Universitas Syiah Kuala, 2019)
Analysis of student needs is an important activity in the process of implementing the BK in order to reach effectiveness, efficiency and achievement of service goals. This study aims to find out the implementation steps of analyzing the needs of students in the preparation of guidance and counseling programs in State Junior High Schools within the Banda Aceh city area. This research includes the type of descriptive research using a qualitative approach. The subjects of this study were BK teachers, principals, homeroom teachers and subject teachers from Banda Aceh State Middle School 1, Banda Aceh Public Middle School 2, Banda Aceh Public Middle School 4 and Banda Aceh State Middle School 17. The data collection technique used is interview. While the data analysis technique is done in three steps, namely data reduction, data display and verification. The results of the study show that; (1) The activity of analyzing the needs of students begins with the preparation stage which includes the needs assessment phase, activities to obtain elements, set the basis for planning; (2) The steps taken by the BK teacher in the activity of analyzing student needs include identification of data, application of instrumentation, collecting data, analyzing / interpreting data and following up; (3) The parties involved in the activity of analyzing the needs of students namely the principal, homeroom teacher and subject teacher.